MODEL RUMAH DIGITAL BERBASIS ARDUINO UNO MENGGUNAKAN MIKROKONTROLER ATMEGA 328P - Hermawan, Rian (STMIK Subang, 2023)
The vulnerability of homeowners is a significant factor in various criminal activities, such as forgetting to lock doors or leaving the house with lights off. Therefore, it is necessary to design a digital home that allows homeowners to control their homes remotely. This research aims to build and enhance a smart home, which has been previously studied. Through this development, the smart home transforms into a digital home by adding several features. The features include Home Door Security, Home Temperature Monitoring, and Home Appliance Control via SMS. The digital home is expected to be beneficial in preventing crimes and addressing negligence-related incidents. By providing access codes to unlock doors, it helps prevent unauthorized entry, enhancing home security. Additionally, it addresses safety concerns related to negligence, such as electrical short circuits or gas leaks that may lead to fires. The digital home can provide immediate assistance by reacting to abnormal temperatures detected by sensors, activating fans to normalize the temperature. If the temperature remains above the specified limit, a danger alarm will sound, indicating an issue inside the house. Another function is the ability to control home appliances remotely via text messages (SMS) when the homeowner is away.